Investigating the electrical properties of zinc oxide nanostructures. - Ravinder Singh (2011)
Electron transport characterisation is fundamental step forward in exploring the potential of a semiconductor material to be used as building material in electronic devices. Several device parameters such as channel length, gate thickness, extent of doping etc. are determined with the help of precise electron transport measurements. Four point probe measurement is considered as one of the reliable electrical characterisation technique especially in case of semiconductor materials. Several key parameters such as resistivity, carrier type, carrier concentration, carrier mobility etc., can be directly calculated to a high degree of accuracy by carefully following simple experimental procedures of four point probe. In this project fundamental electrical characteristic of two different nanostructures (1-D thin films and 2-D nanowires) of ZnO were studied. Resistivity of as grown ZnO thin films is found out to be of the order of 1000 Ocm, post-growth treatment of thin films in the presence of N[2]O environment increases their stability and resistivity is reduced to less than 100 ?cm. This is considered to be due to the N-Zn bonding, as annealing in the presence of O[2] alone resulted in increase in the resistivity. From the measured resistivity of thin films of different thickness it is also established that resistivity of Cu doped ZnO thin films is inversely proportional to the film thickness. An exponential dependence of resistivity on the presence on Cu content in thin film was observed and their resistivity can be easily controlled by varying the percentage of Cu in ZnO thin films. In the case of nanowire devices the resistivity and transconductance measurements were performed using four point probe arrangement to determine the true characteristics of the nanowires. The resistivity of the samples was found out to be in the range of 1.10 x 10[-1] to 5.58 x 10[-2] Ocm. It was observed that with decrease in the width of nanowire beyond 90nm the resistivity decreases because of the decrease in surface vacancies, which result in reduced inelastic scattering events and electron mean free path increases. From the conductance versus gate voltage (Vg) plot, n-type nature of ZnO nanowires is observed. The carrier mobility for the ZnO nanowires was determined to be between 8 and 100 cm[2] /Vs and carrier concentration in the range of 5.66 x 10[17] to 3.77 x 10[19] cm[-3].